1997
DOI: 10.1038/sj.onc.1200973
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of 92 kDa type IV collagenase expression by the jun aminoterminal kinase- and the extracellular signal-regulated kinase-dependent signaling cascades

Abstract: The 92 kDa type IV collagenase (MMP-9), which degrades type IV collagen, has been implicated in tissue remodeling. The purpose of the current study was to determine the role of Jun amino-terminal kinase (JNK)-and extracellular signal-regulated kinase-(ERK)-dependent signaling cascades in the regulation of MMP-9 expression. Towards this end, we ®rst determined the transcriptional requirements for MMP-9 promoter activity in a cell line (UM-SCC-1) which is an avid secretor of this collagenase. Transfection of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
159
1

Year Published

1998
1998
2002
2002

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 221 publications
(176 citation statements)
references
References 42 publications
16
159
1
Order By: Relevance
“…These p38 MAPK and AP-1 expression, binding and transactivation SF Rosenberger et al modi®cations most likely in form of phosphorylation are mediated through an increase in ERK-1/2 activity which is required but apparently not su cient for increased transactivation. These data are consistent with a report by Gum et al (1997) demonstrating a requirement for both ERK-1/2 and JNK in AP-1 mediated collagenase expression.…”
Section: Discussionsupporting
confidence: 93%
“…These p38 MAPK and AP-1 expression, binding and transactivation SF Rosenberger et al modi®cations most likely in form of phosphorylation are mediated through an increase in ERK-1/2 activity which is required but apparently not su cient for increased transactivation. These data are consistent with a report by Gum et al (1997) demonstrating a requirement for both ERK-1/2 and JNK in AP-1 mediated collagenase expression.…”
Section: Discussionsupporting
confidence: 93%
“…In addition, our data are consistent with mounting information (Silberman et al, 1997;Gum et al, , 1997Lengyel et al, 1996Lengyel et al, , 1997 indicating that mitogenic signaling pathways stimulate the upregulation of uPA and MMPs. In this regard, an understanding of the mechanism(s) that tumor cells use to become tumorigenic and govern the production of proteases, which apparently includes the RalA-PLD1 pathway, may prove to be an important target for therapeutic intervention in tumor progression.…”
Section: The Dominant Negative S28n Rala Mutant Prevents Vsrc and V-rsupporting
confidence: 91%
“…Signaling pathways activated by v-Src and v-Ras (Burgering and Bos, 1995) include those involving phosphatidylinositol-3-kinase (Carpenter and Cantley, 1996), protein kinase C (Song et al, 1991), Raf-1 (Blobe et al, 1994) the extracellular regulated kinases (ERK-1 and 2) (Burgering and Bos, 1995) and phospholipase D (PLD) (Song et al, 1991). It has been reported that Raf-1, MEK-1 and ERK1 mediate the signal leading to uPA, uPA receptor, and MMP-9 upregulation Gum et al, 1997). We recently reported that overexpression of uPA in murine mammary adenocarcinoma cells is controlled by a PLD and protein kinase C-dependent pathway (Aguirre Ghiso et al, 1997).…”
Section: Introductionmentioning
confidence: 99%
“…MMP-9 production has been shown to be directly dependent on the activation of endogenous ERK signalling in hepatocyte growth factor-or epidermal growth factor-stimulated human epidermal keratinocytes (Zeigler et al, 1999). Induction of MMP-9 promoter activity by oncogenic Ras in squamous carcinoma cells has been shown to be abrogated by blocking the ERK 1/2 pathway (Gum et al, 1997). Increased transcriptional activity of the MMP-9 promoter in Ras-transformed ovarian carcinoma cells has also been shown to be mediated by MAP kinases (Gum et al, 1996).…”
Section: Discussionmentioning
confidence: 99%